Enhanced methanol tolerance of ZIF-8-immobilized Aspergillus oryzae lipase for biodiesel production from used cooking oil - Xia, Shuaibo; Shen, Cai; Lin, Jiale; Tu, Maolin; Tan, Chin-Ping; Cheong, Ling-Zhi (Elsevier, 2025)
The absorption process of Aspergillus oryzae lipase (AOL) onto the surface of ZIF-8 was elucidated using molecular dynamic (MD) simulation. AOL are absorbed onto the surface of ZIF-8 via hydrogen bonding, electrostatic and van der Waals interaction with minimal changes to its native configurations. Unlike free AOL, AOL@ZIF-8 can maintain its structure in simulated methanol solutions. To verify the results from MD simulation, AOL was immobilized onto ZIF-8 (AOL@ZIF-8: immobilization efficiency of 64.71 % and a protein loading of 57.36 mg/g) and characterized using SEM, FTIR, and XRD. As compared to free AOL, AOL@ZIF-8 demonstrated higher transesterification activity with an activity recovery of 106.18 %. In agreement with MD simulations, AOL@ZIF-8 exhibited enhanced stability in wide range of pH and under presence of alcohol solution. AOL@ZIF-8 can be used to catalyze transesterification of used cooking oil for production of biodiesel (FAME content of 81.19 %).